Determinants of fluconazole resistance and the efficacy of fluconazole and milbemycin oxim combination against Candida parapsilosis clinical isolates from Brazil and Turkey - Daneshnia, Farnaz; Hilmioğlu Polat, Süleyha; Ilkit, Macit; Shor, Erika; de Almeida Júnior, João Nobrega; Favarello, Larissa M.; Colombo, Arnaldo Lopes; Arastehfar, Amir; Perlin, David S. (Frontiers in Fungal Biology, 2022)
Fluconazole-resistant Candida parapsilosis (FLZR-CP) outbreaks are a growing public health concern and have been reported in numerous countries. Patients infected with FLZR-CP isolates show fluconazole therapeutic failure and have a significantly increased mortality rate. Because fluconazole is the most widely used antifungal agent in most regions with outbreaks, it is paramount to restore its antifungal activity. Milbemycin oxim (MOX), a well-known canine endectocide, is a potent efflux pump inhibitor that significantly potentiates the activity of fluconazole against FLZR C. glabrata and C. albicans. However, the FLZ-MOX combination has not been tested against FLZR-CP isolates, nor is it known whether MOX may also potentiate the activity of echinocandins, a different class of antifungal drugs. Furthermore, the extent of involvement of efflux pumps CDR1 and MDR1 and ergosterol biosynthesis enzyme ERG11 and their link with gain-of-function (GOF) mutations in their transcription regulators (TAC1, MRR1, and UPC2) are poorly characterized among FLZR-CP isolates. We analyzed 25 C. parapsilosis isolates collected from outbreaks in Turkey and Brazil by determining the expression levels of CDR1, MDR1, and ERG11, examining the presence of potential GOF mutations in their transcriptional regulators, and assessing the antifungal activity of FLZ-MOX and micafungin-MOX against FLZR and multidrug-resistant (MDR) C. parapsilosis isolates. ERG11 was found to be universally induced by fluconazole in all isolates, while expression of MDR1 was unchanged. Whereas mutations in MRR1 and UPC2 were not detected, CDR1 was overexpressed in three Brazilian FLZR-CP isolates, which also carried a novel TAC1L518F mutation. Of these three isolates, one showed increased basal expression of CDR1, while the other two overexpressed CDR1 only in the presence of fluconazole. Interestingly, MOX showed promising antifungal activity against FLZR isolates, reducing the FLZ MIC 8- to 32-fold. However, the MOX and micafungin combination did not exert activity against an MDR C. parapsilosis isolate. Collectively, our study documents that the mechanisms underpinning FLZR are region specific, where ERG11 mutations were the sole mechanism of FLZR in Turkish FLZR-CP isolates, while simultaneous overexpression of CDR1 was observed in some Brazilian counterparts. Moreover, MOX and fluconazole showed potent synergistic activity, while the MOX-micafungin combination showed no synergy.